THE EFFECT OF ADVERTISING, PERSONAL SELLING, AND SALES PROMOTION TO PURCHASE DECISION OF PRUDENTIAL INDIVIDUAL CUSTOMERS - Annisa Chantya (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims at   examining the effect of Advertising, Personal Selling and Sales Promotion toward Purchase Decision of life insurance business both simultaneously and partially on Prudential customers. The questionnaire has been distributed to 100 respondents who are clients at Prudential life insurance. The sampling technique used is purposive sampling and the research instruments were tested using the   Validity Test, Reliability Test, and Classical Assumption Test. In this research, the data analysis method uses Multiple Regression Analysis. The result of multiple regression analysis shows that Personal Selling has a significant influence on the purchase decision. Meanwhile, it is also found out that Advertising and Sales Promotion do not have a significant influence on the purchase decision. Personal Selling has a partial significant influence and it dominantly affects the purchase decision. Overall, the independent variables of Advertising, Personal Selling and Sales Promotion give significant simultaneous effect on the dependent variable purchase decision. The results of this research can be applied in a marketing strategy for the company and interested parties to maintain and maximize Advertising, Personal Selling and Sales Promotion to obtain a positive effect on potential customers that can lead to a purchase decision.Keywords: Advertising, Personal Selling, Sales Promotion, Purchase Decision